2012
DOI: 10.1021/la300920p
|View full text |Cite
|
Sign up to set email alerts
|

Gemini Imidazolium Surfactants: Synthesis and Their Biophysiochemical Study

Abstract: New gemini imidazolium surfactants 9-13 have been synthesized by a regioselective epoxy ring-opening reaction under solvent-free conditions. The surface properties of these new gemini surfactants were evaluated by surface tension and conductivity measurements. These surfactants have been found to have low critical micelle concentration (cmc) values as compared to other categories of gemini cationic surfactants and also showed the tendency to form premicellar aggregates in solution at sufficiently low concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 72 publications
2
78
0
1
Order By: Relevance
“…The introduction of ester functionality and Cyclohexyloxy in to the hydrophobic tail makes the compound less toxic. Furthermore, the present compounds have also found to be less toxic as compared to earlier synthesized Imidazolium and Pyridinium amphiphiles [3,4]. …”
mentioning
confidence: 52%
See 1 more Smart Citation
“…The introduction of ester functionality and Cyclohexyloxy in to the hydrophobic tail makes the compound less toxic. Furthermore, the present compounds have also found to be less toxic as compared to earlier synthesized Imidazolium and Pyridinium amphiphiles [3,4]. …”
mentioning
confidence: 52%
“…This type of stipulations can be fulfilled only when the degradable reactants used for the synthesis of ionic liquids or introduction of degradable functionality like amide or ester in to the moiety of the resulted product [1,2] or by synthesizing the ionic liquids with high surface activity and low Critical Micelle Concentrations (CMC) [3][4][5]. Ionic liquids (IL s ) have replaced traditional organic solvent, because of low vapor pressure [6,7], high thermal stability, nonflammability and capability to dissolve wide range of compounds [8,9].…”
Section: Introduction Bioactive Peptidesmentioning
confidence: 99%
“…The first breakpoint is due to the formation of premicelles in dilute solutions, while the second breakpoint is the CMC. The existence of premicellar aggregates at low concentration has been previously investigated by several research groups [20][21][22]. Zana has reported that premicellar aggregation is observed in solutions of gemini surfactants with a long alkyl chain of at least 14 carbon atoms [19].…”
Section: Resultsmentioning
confidence: 99%
“…Topological aspects of the condensed complexes have been analyzed by scanning microscopy, such as AFM [91,98]. Other methods as surface tension [99,100], FTIR [96,101], UV-vis [91,102], and some others have been also used to analyze additional aspects of the complexes in the absence of cells.…”
Section: Biophysical Methodsmentioning
confidence: 99%